Analysis of Narrow Slot Loading on a Half Guided Wavelength Folded Substrate Integrated Waveguide - Kumari, Sheelu; Gupta, Vibha Rani; Srivastava, Shweta (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2021)
This paper presents the effects of varying the position, width, and length of a narrow slot loaded onto the central metal septum of a half guided wavelength folded substrate integrated waveguide (FSIW) segment. The study shows that the most significant effect is due to variation in slot length and that slot loading can be used both for bandwidth enhancement/slow-wave effect and filtering, depending on the length of the slot. Both phenomena are explained with the help of field diagrams for different propagating modes and an extracted circuit equivalent to the slot loaded folded substrate integrated waveguide (SFSIW) segment. The results indicate that for the designed FSIW structure, the bandwidth enhancement/slow-wave effect continues until the slot length is 3 mm (0.18 ), beyond which filtering is exhibited. All the developed structures can be used for space/satellite communication. This study will help in deciding the best dimensions of the slot according to the application. The measured scattering parameters of the fabricated structure are compared with the simulated results obtained from the HFSS and the circuit simulator in the ADS and considered to be in good agreement.